γδ T cells are effectors of immunotherapy in cancers with HLA class I defects - de Vries, Natasja L.; van de Haar, Joris; Veninga, Vivien; Chalabi, Myriam; Ijsselsteijn, Marieke E.; van der Ploeg, Manon; van den Bulk, Jitske; Ruano, Dina; van den Berg, Jose G.; Haanen, John B.; Zeverijn, Laurien J.; Geurts, Birgit S.; et al. (Nature (London), 2023)
DNA mismatch repair-deficient (MMR-d) cancers present an abundance of neoantigens that is thought to explain their exceptional responsiveness to immune checkpoint blockade (ICB) 1 , 2 . Here, in contrast to other cancer types 3 – 5 , we observed that 20 out of 21 (95%) MMR-d cancers with genomic inactivation of β2-microglobulin (encoded by B2M ) retained responsiveness to ICB, suggesting the involvement of immune effector cells other than CD8 + T cells in this context. We next identified a strong association between B2M inactivation and increased infiltration by γδ T cells in MMR-d cancers. These γδ T cells mainly comprised the Vδ1 and Vδ3 subsets, and expressed high levels of PD-1, other activation markers, including cytotoxic molecules, and a broad repertoire of killer-cell immunoglobulin-like receptors. In vitro, PD-1 + γδ T cells that were isolated from MMR-d colon cancers exhibited enhanced reactivity to human leukocyte antigen (HLA)-class-I-negative MMR-d colon cancer cell lines and B2M -knockout patient-derived tumour organoids compared with antigen-presentation-proficient cells. By comparing paired tumour samples from patients with MMR-d colon cancer that were obtained before and after dual PD-1 and CTLA-4 blockade, we found that immune checkpoint blockade substantially increased the frequency of γδ T cells in B2M-deficient cancers. Taken together, these data indicate that γδ T cells contribute to the response to immune checkpoint blockade in patients with HLA-class-I-negative MMR-d colon cancers, and underline the potential of γδ T cells in cancer immunotherapy. γδ T cells contribute to the response to immune checkpoint blockade treatment in patients with HLA-class-I-negative DNA mismatch repair-deficient colon cancers. .